The Effect of Sex Differences and Experience of Using Virtual Reality on Presence - Dian Putrawangsa; Clara Theresia; Thedy Yogasara; Yansen Theopilus (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2023)
Presence greatly affects user experience and comfort when using virtual reality (VR). Presence is often associated with personal factors such as sex differences and experience using the instrument. There is a research gap related to presence judging by several studies, so it is an interesting topic for further study. This research aims to identify the effect of sex differences and experience using VR on presence. This study used two approaches namely subjective indicators by employing an Igroup Presence Questionnaire (IPQ) and objective indicators in the form of heart rate (HR) and task scores. The study made use of Kruskal-Wallis and MANOVA to determine whether there is an effect of sex differences and experience in using VR on presence. This study found that the sex variable affects a person's presence when playing VR, especially spatial score on the IPQ test, where women have a higher marginal means value than men. Another finding is that the experience of playing VR affects the delta heart rate, with the result that someone with no experience using VR is higher than those who have used VR before.